NHS Health Checks: Equity and outcomes 2009-17: An observational study. - Robson, J; Garriga-Fuentes, C; Coupland, C; Hippisley-Cox, J (Royal College of General Practitioners, 2021)
Background The NHS Health Check cardiovascular prevention programme is now 10 years old. Aim We describe NHS Heath Check attendance, new diagnoses and treatment in relation to equity indicators. Design and Setting Using a nationally representative database derived from 1,500 general practices 2009-17, we compared NHS Health Check attendance and new diagnoses and treatments, by age, gender, ethnic group and deprivation. Results In 2013-17, 590,218 eligible people age 40-74 years attended an NHS Health Check (16.9%) and 2,902,598 (83.1%) did not attend. South Asian ethnic groups were most likely to attend and women more than men. New diagnoses were more likely in attendees than non-attendees; hypertension 25/1000 attendees vs 9/1000 in non-attendees; type 2 diabetes 8/1000 vs 3/1000; chronic kidney disease 7/1000 vs 4/1000. In people aged 65 or older, new atrial fibrillation was diagnosed in 5/1000 attendees and 3/1000 non-attendees and for dementia 2/1000 versus 1/1000 respectively. Type 2 diabetes, hypertension and CKD were more likely in more deprived groups, South Asian and black African/Caribbean ethnic groups. Attendees were more likely to be prescribed statins, 26/1000, than non-attendees 8/1000; and anti-hypertensive medicines, 25/1000 vs 13/1000 non-attendees. However, of the 117,963 people with 10% or greater CVD risk eligible for statins only 9,785 (8.3%) were prescribed them.